The Damage Control of Liquid Waste Pumping Machines in Palm Oil Companies - Tumanggor, Agustina Hotma Uli; Syarief, Akhmad; Atmana, Fendy Ari (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2021)
X is a company that works in the field of oil palm plantations and has a palm oil production capacity of 60 tons per hour. The products of palm oil that have been produced are Crude Palm Oil (CPO) and Palm Kernel Oil (PKO). The various kinds of waste produced by the company as a result of the palm oil industry process are liquid waste, palm kernels, fiber and seed shells. Liquid waste is used as organic fertilizer for oil palm plantations which will be sent through a liquid waste pump machine. Damage that occurs to the liquid waste pump machine will inhibit the delivery of liquid waste to the plantation, thus affecting the yield of palm oil from the plantation itself. This study describes the application of repair and preventive maintenance policies for liquid waste pump machines by looking at the frequency of damage to the liquid waste pump engine and predicting the delivery of liquid waste to the pump engine for the next period as well as providing solutions for handling damage that occurs in the liquid waste pump engine. From the results of calculations on data processing, the results of how to control the causes of damage that occur in the liquid waste pump machine can be overcome by using the Preventive Maintenance Method within a period of 1 month and maintenance of every component in the liquid waste pump machine within 1 cycle, namely 357.27 hours with a repair time of 5.82 hours. Controlling other causes of damage is to add a filter to the liquid waste pool so that stones, leaves and liquid waste husks do not hinder the suction pipe of the liquid waste pump machine.